Fertility-sparing management of low-grade endometrial stromal sarcoma: analysis of an institutional series, a population-based analysis and review of the literature - Zheng, Yawen (Ann Transl Med, 2020)
BACKGROUND: Low-grade endometrial stromal sarcoma (LGESS) is the second most common malignant mesenchymal tumor of the uterus which usually affects young women. However, the researches on the safety and feasibility of the fertility-sparing management of it are limited. METHODS: A retrospective analysis was performed including 5 women diagnosed with LGESS treated with fertility-sparing management at Qilu Hospital of Shandong University from 2010 to 2019. Besides that, 1,070 patients diagnosed with LGESS in SEER database from 1973 to 2016 were examined. By using the Kaplan–Meier method, survival curves were estimated, and comparisons of statistical signiﬁcance were performed with the stratiﬁed log-rank test within each group. RESULTS: Five patients with LGESS were enrolled in this study. All patients were submitted to fertility-sparing surgeries, after surgery, they all continued hormonal therapy for one year. Four out of the 5 patients recurred, to be more exact, 3 of them recurred in uterus and the other one in the uterus and iliac vascular region. They all suffered further surgery and all 5 patients were alive at the time of last contact. Besides, among these patients, two conceived naturally and delivered a healthy baby by cesarean section. Among 1,070 patients in SEER database, only 28 (2.6%) patients underwent local tumor excision, including excisional biopsy (39%), myomectomy (25%), laser ablation or excision (4%) and polypectomy (4%). There was no statistical signiﬁcance was observed among TH±BSO, radical hysterectomy, subtotal hysterectomy and local tumor excision (P=0.29). CONCLUSIONS: Our analysis indicated that for those young LGESS patients who wish to preserve their fertility, the feasibility and safety of fertility-sparing management should be considered after gynecological oncologist and gynecological pathologist making professional decisions.